Analysis of Knowledge on Clean and Healthy Living Behavior of Kelambir Villagers - Evan Alfian Syahnur; Muhammad Naufal Fathin Hibrizi; Hafidz Yahya Ayyasy; Muhammad Fardhan; Syarbaini Saleh (Universitas Islam Negeri Sumatera Utara, 2023)
Access to clean water, eradicating mosquito larvae, and understanding the impact of smoking at home are crucial factors influencing the health and well-being of communities worldwide. These issues are especially pertinent in areas where knowledge and resources may be limited. The village of Kelambir is one such community where these concerns are paramount. This research aims to shed light on the knowledge and behavior of Kelambir Village residents regarding these key health determinants. Data was collected through questionnaires from 103 respondents interviewed. The results showed that the majority of respondents (89.3%) utilized clean water and had taken proactive steps to eradicate mosquito larvae (69.9%). Despite these positive actions, there were still respondents who depended on unsafe water sources (7.8%) and had not consistently taken measures against mosquito larvae (30.1%). Furthermore, approximately 55.3% of the respondents reported smoking at home, emphasizing a behavior that can significantly increase the risk of respiratory diseases.Keywords: Knowledge, Kelambir Village, PHBS